Disinfeksi Alkaline Peroksida dan Castor Oil 10% terhadap Jumlah Candida Albicans, Kekerasan Permukaan, Stabilitas Warna dan Kekuatan Flexural Nilontermoplastis Dasar Gigi Palsu - Ritonga, Putri Welda Utami (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of soaking thermoplastic nylon denture bases in alkaline peroxide and 10% castor oil on the number of candida albicans, surface roughness, color stability, and flexural strength. This research method is laboratory experimental using thermoplastic nylon. The results showed that there was an effect of alkali peroxide and 10% castor oil on the number of candida albicans for eight days (p = 0.03) and 12 days (p = 0.003), there was no effect on surface roughness for eight days (p = 0.299 ), and there was an effect on surface roughness for 12 days (p=0.09). There was no effect on color stability and flexural strength for eight days and 12 days (p>0.05). This is the diffusion process between alkaline peroxide and castor oil into thermoplastic nylon, castor oil concentration, soaking time, and soaking temperature. In conclusion, drinking thermoplastic nylon denture base in 10% castor oil has the same results as soaking in alkaline peroxide. Keywords: Candida Albicans, Surface Hardness, Flexural Strength, Thermoplastic Nylon, Color Stability